The Mediastinal Mass A Multidisciplinary Approach (Current Clinical Pathology,, 2018)
This book discusses the main approaches for mediastinal mass diagnosis and treatment, whose different aspects have been thoroughly treated by a multidisciplinary team of experts from different clinical fields. The complex anatomy of the mediastinum, as well as the different clinical, radiographic and prognostic features of mediastinal tumors suggests that specialists adopt more flexible and comprehensive practices, as highlighted in this text. The book includes a brief introductory section describing the anatomic sites of mediastinal masses and the epidemiological evidence for each different clinical-pathological entity. In particular, specific chapters are dedicated to thymic tumors, lymphomas, thyroid and parathyroid masses, and germ cell tumors of the anterior mediastinum. The Mediastinal Mass: A Multidisciplinary Approach provides a valuable resource for clinicians, surgeons, radiologists and pathologists dealing with the management and treatment of mediastinal masses through a multidisciplinary approach.